Tools, techniques and protocols for monitoring environmental contaminants - Brar, Satinder Kaur; Hegde, Krishnamoorthy; Pachapur, Vinayak Laxman (Elsevier, 2019)
Tools, Techniques and Protocols for Monitoring Environmental Contaminants describes information on the strategic integration of available monitoring methods with molecular techniques, with a focus on omics (DNA, RNA and protein based) and molecular imprinted polymer and nanomaterial based advanced biosensors for environmental applications. It discusses the most commonly practiced analytic techniques, such as HPLC, MS, GCMS and traditional biosensors, giving an overview of the benefits of advanced biosensors over commonly practiced methods in the rapid and reliable assessment of environmental contaminants. As environmental contaminants have become one of the serious concerns in terms of their rapid growth and monitoring in the environment, which is often limited due to costly and laborious methods, this book provides a comprehensive update on their removal, the challenges they create for environmental regulatory agencies, and their diverse effects on terrestrial and aquatic environments.